Control of Podocyte and Glomerular Capillary Wall Structure and Elasticity by WNK1 Kinase - Liu, Zhenan; Yoon, Joonho; Wichaidit, Chonlarat; Jaykumar, Ankita B.; Dbouk, Hashem A.; Embry, Addie E.; Liu, Liping; Henderson, Joel M.; Chang, Audrey N.; Cobb, Melanie H.; Miller, Richard Tyler (Frontiers in Cell and Developmental Biology, 2021)
Cytoskeletal structure and its regulation are essential for maintenance of the differentiated state of specific types and their adaptation to physiologic and pathophysiologic conditions. Renal glomerular capillaries, composed of podocytes, endothelial cells, and the glomerular basement membrane, have distinct structural and biophysical properties and are the site of injury in many glomerular diseases. Calcineurin inhibitors, immunosuppressant drugs used for organ transplantation and auto-immune diseases, can protect podocytes and glomerular capillaries from injury by preserving podocyte cytoskeletal structure. These drugs cause complications including hypertension and hyperkalemia which are mediated by WNK (With No Lysine) kinases as well as vasculopathy with glomerulopathy. WNK kinases and their target kinases OSR1 and SPAK have fundamental roles in angiogenesis and are activated by calcineurin inhibitors, but the actions of these agents on kidney vasculature and glomerular capillaries are not fully understood. We investigated WNK1 expression in cultured podocytes and isolated mouse glomerular capillaries to determine if WNK1 contributes to calcineurin inhibitor-induced preservation of podocyte and glomerular structure. WNK1 and OSR1/SPAK are expressed in podocytes, and in a pattern similar to podocyte synaptopodin in glomerular capillaries. Calcineurin inhibitors increased active OSR1/SPAK in glomerular capillaries, the Young’s modulus (E) of glomeruli, and the F/G actin ratio, effects all blocked by WNK inhibition. In glomeruli, WNK inhibition caused reduced and irregular synaptopodin-staining, abnormal capillary and foot process structures, and increased deformability. In cultured podocytes, FK506 activated OSR1/SPAK, increased lamellipodia, accelerated cell migration, and promoted traction force. These actions of FK506 were reduced by depletion of WNK1. Collectively, these results demonstrate the importance of WNK1 in regulation of the podocyte actin cytoskeleton, biophysical properties of glomerular capillaries, and slit diaphragm structure, all of which are essential to normal kidney function.